Indagine sull’influenza di differenti sistemi d’allevamento sui connotati nutrizionali, tecnologici, sensoriali e di freschezza dell’orata (Sparus aurata) allevata in Italia - Fagioli, Paolo <1978> (Alma Mater Studiorum - Università di Bologna, 2008)
On account of the commercial importance of gilthead sea bream (Sparus aurata) in Italy the aim of the present study is the evaluation of the quality of nutritional, technological, sensory and freshness aspects. Sea bream production is growing in the Mediterranean and the evaluation of its quality concerns both producers and consumers alike. The culture system greatly influences final product quality. In Italy most of sea bream culture is carried out in cages but there is also a production in land based facilities and in lagoons. In this study external appeareance differentiations are pronounced. Different results were found for nutritional aspects, for fatty acids and for mineral content. Some differences in the freshness indices are also found. Furthermore, organoleptic differences have been described between culture system.